2021
DOI: 10.1007/jhep01(2021)138
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy phenomenology of scalar leptoquarks at one-loop accuracy

Abstract: We perform a complete study of the low-energy phenomenology of S1 and S3 leptoquarks, aimed at addressing the observed deviations in B-meson decays and the muon magnetic dipole moment. Leptoquark contributions to observables are computed at one-loop accuracy in an effective field theory approach, using the recently published complete one-loop matching of these leptoquarks to the Standard Model effective field theory. We present several scenarios, discussing in each case the preferred parameter space and the mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 130 publications
3
71
0
Order By: Relevance
“…It is interesting to remark that with only left-handed interactions, the results of ref. [22] are compatible with our FN power counting for the flavour couplings. With the addition of right-handed interactions, this is no longer the case.…”
Section: Jhep03(2021)122supporting
confidence: 89%
See 4 more Smart Citations
“…It is interesting to remark that with only left-handed interactions, the results of ref. [22] are compatible with our FN power counting for the flavour couplings. With the addition of right-handed interactions, this is no longer the case.…”
Section: Jhep03(2021)122supporting
confidence: 89%
“…In this work we are interested in a scenario with scalar leptoquarks. Previous studies [17][18][19][20][21][22][23][24][25] have shown that the tensions observed in B physics can be accommodated with the two (weak singlet and triplet) hypercharge Y = 1 3 scalar leptoquarks. These scalars are typically referred to in the literature as S 1 and S 3 .…”
Section: Flavour Spurions For Scalar Leptoquarksmentioning
confidence: 99%
See 3 more Smart Citations